Sexual Agency and Sexual Violence Among Female Graduate Students in Iran and Canada: Toward a Model of Sexual Agency - Basmechi, Farinaz (Université d'Ottawa / University of Ottawa, 2026)
In an era of intensified globalization and digital connectivity, discourses surrounding sexual agency and sexual violence against women have gained unprecedented visibility. Yet, persistent structural inequalities continue to constrain practice of women's sexual agency across diverse socio-political contexts. Despite stark differences in legal, cultural, and institutional regimes, women in liberal democratic settings such as Canada and highly restrictive regulatory contexts such as Iran continue to experience high rates of sexual violence and comparable barriers to exercising sexual agency. This paradox raises a central question: how and why do women's sexual lives and vulnerabilities converge across such divergent geopolitical contexts? This study examines the lived experiences of female graduate students in Iran and Canada, focusing on sexual agency, sexual pleasure, sexual violence, and the role of state and institutional policies, with particular attention to the effects of the COVID-19 pandemic. The pandemic constituted a global moment of intensified state intervention, social isolation, and digital reliance, exacerbating pre-existing gendered inequalities. In Canada, reported sexual violence increased by approximately 20-30 percent during the pandemic. Comparable dynamics were observed globally, including in Iran, where the absence of protective policies, combined with restrictive legal and religious regulations, further constrained women's sexual autonomy and safety. Graduate students, situated at the intersection of gender, age, academic precarity, and economic vulnerability, remain significantly underexamined in the literature, particularly within comparative and non-Western frameworks. Guided by a hybrid theoretical framework that integrates feminist materialism, intersectionality, and biopolitical analysis, this study addresses four research questions: (1) how female graduate students in Iran and Canada experience and enact sexual agency and sexual pleasure; (2) how state and institutional protective and preventive policies shape their sexual practices; (3) the forms of sexual violence they encounter and the ways in which university and state policies influence these experiences; and (4) how the COVID-19 pandemic transformed their sexual lives and exposure to sexual violence across the two contexts. Employing a qualitative comparative design, the study draws on in-depth interviews with 31 graduate women aged 25-45 in the humanities and social sciences at the University of Ottawa (n = 16) and the University of Tehran (n = 15). This comparative analysis demonstrates how variations in legal, cultural, and institutional environments shape sexual agency, lived experiences, and exposure to sexual violence, as well as the strategies women use to navigate, resist, and respond to these conditions. The findings reveal that female graduate students in Iran and Canada experience sexual agency, intimacy, and sexual violence in strikingly similar ways, despite profound differences in political and legal governance. In both contexts, women's sexual lives are structured by patriarchal neoliberal capitalism, which appropriates women's emotional labor, time, and bodily availability through dating cultures and intimate relationships. Sexual relationships are shaped by emotional capitalism and social acceleration, generating precarious, competitive, and gendered expectations that disproportionately burden women. In Canada, formal policies and discourses of sexual liberation have not dismantled patriarchal power relations; rather, participants described their reconfiguration through media, informal sexual education, and neoliberal market logics. In Iran, sexuality is overtly regulated through legal, religious, and biopolitical mechanisms. Nevertheless, women actively navigated and resisted these constraints, particularly through digital platforms used for dating and intimacy, while simultaneously expressing deep mistrust toward state and institutional authorities perceived as punitive rather than protective. Across both settings, intersecting forms of marginalization, including economic precarity, migrant status, and sexual orientation, significantly heightened vulnerability to coercion and sexual violence. Sexual agency emerged as a dynamic, evolving process rather than a fixed capacity, resulting in four empirically identified forms: habituated traditional, anomic, updated conflicted, and liberated. Patterns of sexual violence were largely comparable across contexts, with street harassment more prevalent in Iran and institutional and workplace violence more prominent in Canada. The COVID-19 pandemic intensified these risks in both countries, while institutional responses remained limited, underscoring the structural and systemic nature of sexual violence beyond policy reform alone.
Keywords: Sexual agency; Sexual violence; Dating and Intimacy; Female graduate students; Patriarchal capitalism; Neoliberalism; Intersectionality; COVID-19; Iran; Canada